PENGARUH LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS TERHADAP HARGA SAHAM PERUSAHAAN OTOMOTIF BEI (2022–2024) - Devi Lastina; Hasim As'ari (JURNAL ILMIAH EDUNOMIKA, 2026)
This study was conducted to determine and analyze the effect of liquidity, solvency, and profitability on the stock prices of automotive companies on the Indonesia Stock Exchange (IDX) (2022-2024). The population in this study were all automotive and component manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Samples were obtained from automotive and component manufacturing companies listed on the Indonesia Stock Exchange (IDX) and had accessible annual financial reports for the period 2022 to 2024, with the criteria for selecting samples of financial reports in Automotive and Component Companies listed on the Indonesia Stock Exchange that have been published during 2022–2023. The company has consistent financial report data from 2022–2024. Reports financial reports in rupiah currency. And, reports financial reports in profit conditions. The data analysis technique used SPSS. The results of the study showed that liquidity has a significant effect on stock prices and can be accepted. Thus, H0 is rejected and H1 is accepted. The results of this study show that the t-test calculation for the independent variable measured using the Debt-to-Equity Ratio (DER) significantly influences stock prices, with a significance value of <0.001 <0.05 and a t-value of -5.100. Therefore, the hypothesis that solvency influences stock prices is accepted. The t-test results indicate that the profitability variable (Return on Assets) significantly influences stock prices, with a significance value of 0.002 <0.05 and a t-value of 3.430. Therefore, H3, which states that profitability influences stock prices, is accepted.